Network Pharmacology Analyses of the Pharmacological Targets and Therapeutic Mechanisms of Salvianolic Acid A in Myocardial Infarction. (5th October 2022) - Huang, Qing; Zhang, Chao; Tang, Shaoyong; Wu, Xiaoyan; Peng, Xiong
Abstract : Objective . Salvianolic acid A, a natural polyphenolic ingredient extracted from traditional Chinese medicine, possesses an excellent pharmacological activity against cardiovascular diseases. Herein, therapeutic mechanisms of salvianolic acid A in myocardial infarction were explored through systematic and comprehensive network pharmacology analyses. Methods . The chemical structure of salvianolic acid A was retrieved from PubChem database. Targets of salvianolic acid A were estimated through SwissTargetPrediction, HERB, and TargetNet databases. Additionally, by GeneCards, OMIM, DisGeNET, and TTD online tools, myocardial infarction-relevant targets were predicted. Following intersection, therapeutic targets were determined. The interaction of their products was evaluated with STRING database, and hub therapeutic targets were selected. GO and KEGG enrichment analyses of therapeutic targets were then implemented. H9C2 cells were exposed to oxygen‐glucose deprivation/reoxygenation (OGD/R) to mimic myocardial infarction and administrated with salvianolic acid A. Cellular proliferation was assayed via CCK‐8 assay, and hub therapeutic targets were verified with RT-qPCR. Results . In total, 120 therapeutic targets of salvianolic acid A in myocardial infarction were identified. There were close interactions between their products. Ten hub therapeutic targets were determined, covering SRC, CTNNB1, PIK3CA, AKT1, RELA, EGFR, FYN, ITGB1, MAPK8, and NFKB1. Therapeutic targets were significantly correlated to myocardial infarction-relevant pathways, especially PI3K-Akt signaling pathway. Salvianolic acid A administration remarkably ameliorated the viability of OGD/R-induced H9C2 cells, and altered the expression of hub therapeutic targets. Conclusion . Our work uncovers therapeutic mechanisms of salvianolic acid A for the treatment of myocardial infarction, providing a new insight into further research on salvianolic acid A.